Kecerdasan Buatan di Kelas Pengajaran Bahasa Inggris: Penggunaan HyperWrite sebagai Alat Menulis untuk Meningkatkan Proses Penulisan - Alfi Hidayatu Miqawati; Fitri Wijayanti; Ihwan Huda Al-Mujib; Agus Setia Budi; Suyik Binarkaheni (CV. Sakura Digital Nusantara, 2026)
Purpose – AI-powered writing tools offer innovative breakthroughs by automating aspects of the writing process and providing helpful suggestions and feedback, thereby potentially improving writing outcomes and efficiency. This paper discusses the integration of HyperWrite in supporting and enhancing the writing process in ELT classrooms. Methods – A qualitative research method using library study approach was deployed to formulate ideas about the implementation of HyperWrite in writing classes. The sources of data vary from journals, research reports, official documents, and curriculum. The data were analyzed through several steps that involved data reduction, data display, and conclusion drawing. Findings – Several studies highlighted that HyperWrite has established itself as a potent tool among AI writing assistants, featuring a multifaceted platform that helps with both the efficiency and the quality of writing. It uses advanced machine learning algorithms to guide users in all aspects of writing, which include developing ideas and editing final drafts. This study also highlights the implementation of HyperWrite to guide students to write effectively.Research implications – The use HyperWrite in ELT writing classes suggests a shift in the teacher’s role toward that of a facilitator who guides students in critically evaluating AI suggestions, while also fostering the development of critical thinking and self-confidence among students. Furthermore, these findings call for the integration of AI literacy into the ELT curriculum to develop students’ competence to use, evaluate, and edit AI-generated work ethically. This study was limited to only one AI tools and further studies about the uses of other tools for ELT classrooms are recommended. Originality – This study offers a novel approach by conducting an integrated examination of the role of teachers, students’ critical thinking, and HyperWrite-assisted ELT writing classroom.